Work and Universal Basic Income (Polis (Santiago), 2022)
The Universal Basic Income has been formulated as a free and universal salary standard that partially resolves the injustice due to labor exploitation and labor alienation caused by the means of production, whether these are managed by natural people or the State itself. It seems that the term “work” plays an important role in this political theory. Moreover, after studying the path from Aristotle to Marx, it conveys the impression that these are foundations by others, such as justice or injustice. Thus, the partial extension of the solution granted by UBI seems to be unclear given the alienation of societies where individuals alienate their own work, their product, and consequently, the whole of social life. When elucidating these problems from the Philosophy of Political Science we are allowed to better consider such limitations, flexibility and possibilities of implementation. Hence, UBI turns out to be an advance that can be essential to achieve greater justice and freedom.
Keywords: Politics; exploitation; justice; alienation; philosophy.